Entre madres-adolescentes y adolescentes-madres: un análisis de su trayectoria de vida y los factores que influyen en su configuración - Mastro Naccarato, Irene Del (2015)
The main objectives of this research, that took place in Lima between 2012 and 2013, were to analyze: a) the consequences of teenage motherhood in education, labor and family and b) the factors that influence the reconfiguration of the life trajectories of the teenage mothers after the pregnancy period. After interviewing thirteen teenage mothers that come from different socioeconomic backgrounds and whose children age range between 2-5 years old, we find two types of trajectories: a) the teenage mother trajectory and b) the teenage as mother trajectory. The results of this research suggest that the socioeconomic background, gender, teenage culture and motherhood, as well as the experiences, characteristics and aspirations of each woman are key factors that shape the life trajectories of teenage mothers.